Predicción temporal de CD4+ en 80 pacientes con manejo antirretroviral a partir de valores de leucocitos - Javier Rodríguez-Velásquez (Asociación Colombiana de Infectología, 2020)
Objective: To establish a predictive methodology of CD4+ counts for clinical application in ranges of clinical interest based on the absolute leukocyte count. Methodology: From sequential values of leukocytes and CD4+ lymphocytes of nine patients, mathematical patterns were observed and applied in a blind study with 71 cases to confirm their predictive capacity, measuring percentages of specificity and sensitivity. Results: Five mathematical patterns were determined that predict 99% of the cases in which CD4+ counts are obtained from leukocyte counts with specificity and sensitivity values of 99%. Conclusions: The mathematical patterns found between leukocytes and CD4 counts suggest that this phenomenon is practically deterministic.